THE DETERMINING OF THE BOSPHORUS BRIDGES EFFECTS ON URBAN GROWTH USING SIMULATION - Ayazli, Ismail Ercument; Kilic, Fatmagl; Demir, Hulya (YILDIZ TECHNICAL UNIV, 2013)
Istanbul, which joins two continents-Asia and Europe, is an important city with its cultural, natural and environmental heritages. After the 1950's, increasing population and rapid urban growth have caused an enormous transportation problem. To overcome this problem, Bosphorus Bridge was built in 1973 and Fatih Sultan Mehmet Bridge in 1988. In a short time after the building of two bridges, each bridge created its own traffic and triggered urbanization to northward in Istanbul. The main purpose of this paper is to determine land use changes driven by Bosphorus bridges. In this study, remote sensing, geographic information systems (GIS), simulation and other statistical methods were used together. In the region that covered Bosphorus Bridges routes and their accessed roads, land use classes were classified from Landsat imagery for the years 1972, 1987, 2002 and 2009. The transportation data for the years 1972 and 1987 were digitized from Landsat imagery and the third one for the year 1997 was obtained from Istanbul Metropolitan Municipality. Excluded areas were produced using satellite imagery, maps and plans and urban growth simulation model was created using cellular automata (CA) algorithm. Land use changes between 1972 and 2009 were determined through change detection analysis using with SLEUTH urban growth simulation software. According to the results, a 28% decline was determined in the forest areas whereas a 30% increment was detected in the settlement areas.
Keywords: Geographic information systems; remote sensing; simulation; urban growth; Engineering